Surviving the Scene in Civilian Penetrating Brain Injury: Injury Type, Cause and Outcome in a Consecutive Patient Series in Austria - Marhold, Franz; Scheichel, Florian; Ladisich, Barbara; Pruckner, Philip; Strasser, Elisabeth; Themesl, Melanie; Ungersboeck, Karl; Popadic, Branko (Frontiers in Surgery, 2022)
Background: Penetrating brain injury (PBI) is a heterogeneous condition with many variables. Few data exist on civilian PBI. In some publications, PBI differentiation between low- and high velocity injury (LVI, HVI) is made, but exact definitions are not made yet. The incidence of PBI depends heavily on the country of origin. Furthermore, captive bolt pistol (CBP) injuries represent a rare type of LVI and almost no reports exist in the human medical literature. Treatment of PBI has been controversially discussed due to high morbidity and mortality with results varying considerably between series. Prognostic factors are of utmost importance to identify patients who presumably benefit from treatment. Methods: A retrospective, single-center analysis of a consecutive patient series was performed from September 2005 until May 2018. We included all patients with PBI who reached our hospital alive and received any neurosurgical operative procedure. Results: Of a total of 24 patients, 38% died, 17% had an unfavourable outcome and 46% had a favourable outcome. 58% of patients with PBI were self-inflicted. Leading cause of injury were firearms, while captive bolt pistols were responsible for 21%. LVI represented 54% and HVI 46%. Outcome in HVI was significantly worse than in LVI. Favourable outcome was achieved in 69% of LVI and 18% of HVI. Low GCS and pathological pupillary status at admission correlated significantly with unfavourable outcome and death. Conclusions: PBI is a heterogeneous injury with many variables and major geographical and etiological differences. Differentiation between LVI and HVI is crucial for decision making and predicting outcome. In patients presenting with object trajectories crossing the midline no favourable outcome could be achieved. Nevertheless, in total a favourable outcome was possible in almost half of the patients who succeed to surgery.